Understanding death an introduction to ideas of self and the afterlife in world religions - Sumegi, Angela 1948- (Wiley Blackwell, 2014)
"A comprehensive survey of how religions understand death, dying, and the afterlife, drawing on examples from Christian, Jewish, Hindu, Buddhist, and Shamanic perspectives. Considers shared and differing views of death across the world's major religions, including on the nature of death itself, the reasons for it, the identity of those who die, religious rituals, and on how the living should respond to death; Places emphasis on the varying concepts of the 'self' or soul; and uses a thematic structure to facilitate a broader comparative understanding."--Publisher's website.